Zoper "naravni" red sveta - Kernev-Štrajn, Jelka (Primerjalna književnost, 2016)
From the perspective of the late philosophy of Gilles Deleuz and Félix Guattari, and especially from the perspective of their notions: sign, representation, becoming, animal, encounter, coincidence, and many others, this article focuses on the modern Polish novel Prowadź swój pług przez kości umarłych (Drive Your Plough over the Bones of the Dead). It examines the thematization of non-anthropocentric orientation, clearly visible in the novel, and the fact that William Blake's compositive art is the main intertextual element of the novel. In this regard, it explores the surprising common points and literary thematization of the intersections between Blake's world and artistic views and the philosophical thinking of Deleuze and Guattari.
Keywords: Deleuze, Gilles, 1925-1995; Guattari, Félix, 1930-1992; Tokarczuk, Olga, 1962-; Blake, William, 1757-1827; filozofija jezika; znak; reprezentacija; Polish literature; poljska književnost; angleška poezija; človek in žival; neantropocentričnost